Agreement between capillary and venous lactate in emergency department patients: prospective observational study. Issue 4 (3rd April 2019) - Graham, Colin A; Leung, Ling Yan; Lo, Ronson SL; Lee, Kwok Hung; Yeung, Chun Yu; Chan, Suet Yi; Cattermole, Giles N; Hung, Kevin KC
Abstract : Objectives: Capillary blood lactate testing with handheld analysers has great advantages to reduce the time needed for clinical decisions, and for extended use in the prehospital setting. We investigated the agreement of capillary lactate measured using handheld analysers (CL-Nova and CL-Scout+ measured by Nova and Lactate Scout+ analyzers) and the reference venous level assessed using a point-of-care testing (POCT) blood gas analyser (VL-Ref). Design: A prospective observational study. Setting: A university teaching hospital emergency department in Hong Kong. Participants: Patients triaged as 'urgent' (Category 3 of a 5-point scale), aged ≥18 years during 2016 were eligible. 240 patients (mean age 69.9 years) were recruited. Primary and secondary outcome measures: The primary outcome measure was the agreement of the capillary blood lactate level measured by handheld lactate analyser when compared with the reference standard technique, namely venous blood samples obtained by venepuncture and analysed using the blood gas analyser. The secondary outcome measure was the difference in values of venous lactate using blood gas analysers and handheld lactate analysers. Results: The results of VL-Ref ranged from 0.70 to 5.38 mmol/L (mean of 1.96 mmol/L). Regarding capillary lactate measurements, the bias (mean difference) between VL-Ref and CL-Scout+ was −0.22 with 95% limits of agreement (LOA) of −2.17 to 1.73 mmol/L and the bias between VL-Ref and CL-Nova was 0.46, with LOA of −1.08 to 2.00 mmol/L. For venous lactate, results showed the bias between VL-Ref and VL-Scout+ was 0.22 with LOA being −0.46 to 0.90 mmol/L, and the bias between VL-Ref and VL-Nova was 0.83 mmol/L with LOA −0.01 to 1.66 mmol/L. Conclusion: Our study shows poor agreement between capillary lactate and reference values. The study does not support the clinical utility of capillary lactate POCT. However, venous lactate measured by Scout+ handheld analyser may have potential for screening patients who may need further testing. Trial registration number: NCT02694887 .